2018
DOI: 10.1186/s13104-018-3372-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with amputation among patients with diabetic foot ulcers in a Saudi population

Abstract: ObjectivesA prospective study was conducted at the Armed Forces Hospital, Dhahran, Saudi Arabia, between January 2015 and December 2016 to identify the risk factors associated with amputation among diabetic foot ulcers DFUs patients.ResultsIn total, 82 patients were recruited. Fifty-five of the patients were males (67.07%), the mean (SD) age of the participants was 60 (± 11.4) years, the mean duration of diabetes was 8.5 (± 3.7) years, and the mean haemoglobin A1c was 4.8 (± 2.8)%. In Univariate analysis, olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 28 publications
4
23
1
Order By: Relevance
“…The mean age of the study participants was 56.8 (±12.4) years with about 90% of them aged above 40 years. In the same vein, Al-Rubeaan et al 11 in their retrospective cohort study have reported that “age ⩾45 years is a risk factor for developing diabetic foot ulcers in a Saudi population.” Similarly, more recently, Musa et al 29 in their study of the factors associated with amputation among patients with DF ulcers in the same population highlighted that the “worldwide metabolic syndrome epidemic,” which is particularly affecting the Arabian Gulf area, could be responsible for the younger age of presentation.…”
Section: Discussionmentioning
confidence: 96%
“…The mean age of the study participants was 56.8 (±12.4) years with about 90% of them aged above 40 years. In the same vein, Al-Rubeaan et al 11 in their retrospective cohort study have reported that “age ⩾45 years is a risk factor for developing diabetic foot ulcers in a Saudi population.” Similarly, more recently, Musa et al 29 in their study of the factors associated with amputation among patients with DF ulcers in the same population highlighted that the “worldwide metabolic syndrome epidemic,” which is particularly affecting the Arabian Gulf area, could be responsible for the younger age of presentation.…”
Section: Discussionmentioning
confidence: 96%
“…This finding was comparable with Al-Rubeaan et al [7] in their retrospective cohort study where they reported that “age ≥ 45 years is a risk factor for developing diabetic foot ulcers in Saudi population”. Similarly, in the study about the factors associated with amputation among DF ulcer patients in Saudi population, Musa and his colleagues [16], recently highlighted the “epidemic of metabolic syndrome around the world”, which particularly affects the Gulf region, being responsible for a younger age at the onset of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…10 Musa, et al (2018) found that old age was the risk factor for lower extremity amputation in diabetic foot patients. 6 They stated that elderly patients had poor prognosis in wound healing because of a reduced immune response to infection and other comorbid diseases that slowed wound healing. 6 The difference in this study could be caused due to differences in the number of samples used.…”
Section: Discussionmentioning
confidence: 99%
“…6 They stated that elderly patients had poor prognosis in wound healing because of a reduced immune response to infection and other comorbid diseases that slowed wound healing. 6 The difference in this study could be caused due to differences in the number of samples used. The sample in this study did not meet the minimum sample of 23 patients for each group so that the results could be affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation